Evaluasi Pengelolaan Aset Tidak Lancar Pemerintah Daerah Berdasarkan Peraturan Menteri Dalam Negeri Nomor 19 Tahun 2016 (Studi Kasus Pada Sekretariat Kota Administrasi Jakarta Pusat) - Moch Makruf Deni Setiawan; Pandoyo Pandoyo (Jurnal Ilmu Administrasi Publik, 2022)
This study aims to understand how the Non-Current Assets of the Secretariat of Central Jakarta Administration City is managed and evaluated, and to identify the encountered constraints and solutions taken to cope with such obstacles. The study also has objectives of providing an evaluation model in Non-Current Asset Management under the Regulation of the Minister of Home Affairs Number 19 of 2016 concerning Guidelines in the Management of Regionally Owned Assets, while offering some improvements in the management of Local Government non-current assets. The study adopts descriptive quantitative method with data collection using interview, observation, documentation and internet searching techniques. The study shows that the local government non-current assets at the Secretariat of Administration City Central Jakarta have been soundly managed in accordance with the Regulation of the Minister of Home Affairs Number 19 of 2016 despite some shortcomings in terms of Asset Need and Budgeting Assessment, Asset Write-Offs, and lack of human resources. These weaknesses have been dealt with solutions as offered by the author in this scientific essay.